Aplicação de um protocolo de mobilização, baseado no nivel funcional, em pacientes submetidos à cirurgia cardíaca: ensaio clínico, controlado e randomizado - BORGES, Mayara Gabrielle Barbosa (2022)
Patients undergoing cardiac surgery may present functional changes in the postoperative period. Several physiotherapeutic interventions have been described aiming to minimize the functional loss related to the surgical procedure. However, they present as a limitation the use of generalist protocols that are not based on the individuality of patients. Thus, this research proposes to verify the effects of the application of an adapted mobilization protocol, based on the functional level, on mobility, peripheral muscle strength, length of stay in the Intensive Care Unit (ICU) and hospital of patients undergoing cardiac surgery. We conducted a randomized controlled trial with adult patients (18 to 60 years old), of both sexes, who underwent cardiac surgery from January 2020 to June 2021. Patients were evaluated regarding: (i) time, in hours, to achieve mobilization milestones (bedside sitting, out of bed sitting, standing and walking); (ii) level of mobility, using the ICU Mobility Scale (IMS); (iii) peripheral muscle strength, using hand grip dynamometry; and (iv) length of stay in the ICU and hospital. Participants were randomized into two groups: a control group (conventional mobilization protocol) and an intervention group (functional level-based mobilization protocol). The intervention protocol was adapted from the study by Hodgson et al. (2016), based on the IMS level, and the conventional protocol, as recommended by Winkelmann et al. (2015). In chapter 1, we provide, through a systematic review, the description of exercise prescription in patients undergoing cardiac surgery. In conclusion, most protocols are generalist, progressive, low intensity, with frequency of twice a day and duration of 10 to 30 minutes. In chapter II, the impact of an individualized protocol on the mobility of patients undergoing cardiac surgery compared to the conventional protocol was evaluated. No statistically significant differences were found in the two types of protocol regarding mobilization milestones and mobility level, peripheral muscle strength, length of stay in the Intensive Care Unit (ICU) and hospital comparing the protocols.